PENERAPAN STRATEGI PEMBELAJARAN BERDIFERENSIASI DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK MENINGKATKAN MINAT BELAJAR SEJARAH SISWA KELAS XI IPS 1 SMA NEGERI 19 PEKANBARU - Bunga Berliana S, Camila Lovendra, Oriza Septiva; Vivi Nursoviyanti, Ahmal, Agusmir (STKIP Subang, 2025)
This research is a classroom action research (CLASROOM ACTION REPORT) which aims to increase interest in learning history subjects through differentiated learning with the Culturally Responsive Teaching (CRT) approach in class XI IPS 1 at SMA Negeri 19 Pekanbaru. The research was conducted in 4 stages, namely planning, implementation, observation and reflection. The number of cycles carried out in this study was two cycles and each cycle consisted of two meetings. Data collection methods were by observation and questionnaire techniques. Data analysis using descriptive and quantitative analysis techniques. The results of this study showed that there was an increase in the number of students' interest in learning history in cycle I by 67.86% with the criteria of not yet successful and in cycle II there was an increase with a score of 87.10%. With this it can be interpreted that students' interest in learning has reached the success indicator of 80%. The results of the observational study showed that there was an increase in the learning interest of class XI IPS 1 students. The conclusion of the research results supports the research hypothesis that differentiated learning with the CRT approach can increase students' learning interest in the history subject of class XI IPS at SMA Negeri 19 Pekanbaru.